The Functions And Linguistic Analysis Of Metaphor In The Holy Qur’an - Ali Al-Ali; Ahmad El-Sharif; Mohamad Sayel Alzyoud (European Scientific Journal, ESJ, 2016)
The paper aims to tackle the function of metaphor in the Qur’an within the theoretical framework put forward by Lakoff & Turner (1989). This theory is known as the Cognitive Theory of Metaphor. It shows how the Qur’an is structured around the idea of the variety of meaning of lexical items, and how every correspondence between the two domains of “literal” and “non-literal” can fit into it. However, such an application of cognitive semantic approach can provide valuable insights. These insights enhance the overall aim of this paper which is to prove the linguistic creativity of the Qur'an through applying the cognitive theory of metaphor. This paper outlines the basis from which the Qur'an should be considered not only as a book of religious teachings, but also as a linguistic miracle for Arabs (Elsharif, 2011). The structure of this paper is presented as follows. First, we introduce the theoretical background and arguments of this study. Afterwards, we underline the significance of this study and its contribution to the field. In the following section, we present the definition and function of metaphor. Next, we embark on the linguistic analysis of metaphor in the holy Qur’an, metaphorical language and its use in discourse, and metaphor and Islamic religious discourse. Finally, we end the essay with a concluding paragraph.